News Items About the Use of Medical Assistance in Dying Raise Concerns About the System in Canada - Straube, Sebastian; Els, Charl; Fan, Xiangning (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
Several recent news items discuss cases where medical assistance in dying seems to be sought not because the medical situation is beyond hope despite optimal supports, but rather because supports that could theoretically be available are inaccessible in practice or, if accessible, are apparently insufficient. We discuss these developments.